2021
DOI: 10.21608/ejchem.2021.88640.4262
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Adding MWCNTs on the Hardness, Impact Strength, and Structural Properties of Composite Materials based on Epoxy Polymer

Abstract: This research focuses on using Multiwalled carbon nanotubes to successfully produce MWCNTs/Epoxy nanocomposite with various MWNT weight loadings (0.25,0.50,1and2 % wt.). The samples were manufactured by utilizing an ultrasonic machine and a solution mixing method (MIT). The characterization, mechanical characteristics, and morphology of the resulting MWCNTs/Epoxy nanocomposites were investigated using FTIR, hardness, impact testing, and FE-SEM. According to the findings, different MWCNT loadings enhanced the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…% of MWCNTs was better than epoxy, but lower than 0.8 wt.%, due to the low content of the nanotubes, as did not provide the epoxy with the required strength. Adding 1 wt.% of MWCNT was better than that of epoxy, but lower than 0.8 wt.% because of forming agglomerates of MWCNT in the epoxy, which results in lowering the strengthening effects of the MWCNT (Fadhil et al, 2016) where the agglomerates also serve as planes where cracks can easily spread and slip, which causes material breakage even at low mechanical loads (Mateab and Albozahid, 2022). Adding 0.8 wt.% of MWCNT to epoxy was the best among the others because this percentage was high enough to strengthen the matrix without causing tube tangling and agglomeration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…% of MWCNTs was better than epoxy, but lower than 0.8 wt.%, due to the low content of the nanotubes, as did not provide the epoxy with the required strength. Adding 1 wt.% of MWCNT was better than that of epoxy, but lower than 0.8 wt.% because of forming agglomerates of MWCNT in the epoxy, which results in lowering the strengthening effects of the MWCNT (Fadhil et al, 2016) where the agglomerates also serve as planes where cracks can easily spread and slip, which causes material breakage even at low mechanical loads (Mateab and Albozahid, 2022). Adding 0.8 wt.% of MWCNT to epoxy was the best among the others because this percentage was high enough to strengthen the matrix without causing tube tangling and agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Low impact energy, or the capacity of composite materials to absorb and reduce energy during fracture propagation, is influenced by the filler content. However, in the case of a thermoset-toughened polymer, the thermoset's presence effectively causes stress redistribution in the composite, leading to microcracking or crazing at various areas, resulting in a more efficient energy dissipation mechanism (Mateab and Albozahid, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…To fabricate fibers that are not only non-woven meshes but also aligned, patterned, twisted yarn, and three-dimensional structures, developing new methods for controlling the deposition behavior of the fibers either by mandrel collector shaft, rotating drums, disk collectors or parallel electrodes are required [10,11] Xie, et at ,(2010) used the opposite charge nozzle's to align 3-D nanofibers into a uniaxial array. They modified the typical set-up by installing two needles in opposite directions and pumping the polymer solution into needles by two syringe liquid pumps with the same injection rate [12]. Aligned and molecularly oriented Polyacrylonitrile nanofibers were prepared using a nonconventional approach, that is using two needles in opposite positions and a rotating collector perpendicular to needle axis [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Mostafavi [18] found that applying silane-treated epoxy nanocomposites nano zinc dioxide up to 0.5% wt., will provide higher impact strength and fracture toughness than the neat epoxy. Some authors [19,20] prepared ZnO-epoxy nanocomposites at different contents, and studied their surface morphology and curing behavior. It was revealed that the micro-hardness of epoxy-nanocomposites was significantly reduced at the loading which the epoxy curing was not complete.…”
Section: Introductionmentioning
confidence: 99%